The non-designer's design book : design and typographic principles for the visual novice - Williams, Robin, ....- (Berkeley (Calif.) : Peachpit, 2008)
A lot has happened in the world of digital design since the first edition of this title was published, but one thing remains true: There is an ever-growing number of people attempting to design pages with no formal training. This book is the one place they can turn to find quick, non-intimidating, excellent design help from trusted design instructor Robin Williams. This revised classic - now in full color - includes a new section on the hot topic of Color itself. In The Non-Designer's Design Book, 3rd Edition, Robin turns her attention to the basic principles that govern good design. Readers who follow her clearly explained concepts will produce more sophisticated and professional pages immediately. Humor-infused, jargon-free prose interspersed with design exercises, quizzes, and illustrations make learning a snap - which is just what audiences have come to expect from this best-selling author.
Keywords: Typografie